2022
DOI: 10.1542/peds.2022-057989
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report: Breastfeeding and the Use of Human Milk

Abstract: Breastfeeding and human milk are the normative standards for infant feeding and nutrition. The short- and long-term medical and neurodevelopmental advantages of breastfeeding make breastfeeding or the provision of human milk a public health imperative. The American Academy of Pediatrics (AAP) recommends exclusive breastfeeding for ∼6 months after birth. Furthermore, the AAP supports continued breastfeeding, along with appropriate complementary foods introduced at about 6 months, as long as mutually desired by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 173 publications
1
61
0
Order By: Relevance
“…The American Academy of Pediatrics (AAP) and the World Health Organization recommend exclusive breastfeeding (or feeding mother's expressed milk) for the rst six months of age and to continue breastfeeding along with appropriate complementary foods introduced at about 6 months, as long as mutually desired by mother and child for 2 years or beyond (15,16). The AAP recommends pasteurized donor human milk if a mother's own milk is not available or contraindicated (17). If mother's own milk or pasteurized donor milk are not available, infant formula is the next nutritionally adequate and safe option to feed infants.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Pediatrics (AAP) and the World Health Organization recommend exclusive breastfeeding (or feeding mother's expressed milk) for the rst six months of age and to continue breastfeeding along with appropriate complementary foods introduced at about 6 months, as long as mutually desired by mother and child for 2 years or beyond (15,16). The AAP recommends pasteurized donor human milk if a mother's own milk is not available or contraindicated (17). If mother's own milk or pasteurized donor milk are not available, infant formula is the next nutritionally adequate and safe option to feed infants.…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence from epidemiological and biological studies has emphasized the propitious health effects of breastfeeding [ 1 ]. However, the prevalence of breastfeeding is often influenced by many factors, such as socio-demographic features, mode of delivery, early time of first breastfeeding, and the presence of personnel trained and skilled to support human lactation, which has been demonstrated to be essential for both the initiation and longer duration of breastfeeding [ 2 , 3 , 4 , 5 ]. The American Academy of Pediatrics (AAP), in consistence with guidelines and policies of the World Health Organization (WHO) both recommend that infants be exclusively breastfed for approximately 6 months; and furthermore, support continuing breastfeeding for 2 years or beyond, in order to induce the optimal short- and long-term outcomes for the mother–child dyad [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, the American Academy of Pediatrics (AAP), the World Health Organization (WHO), and the American Academy of Family Physicians (AAFP) jointly released a new list of guidelines recommending extended breastfeeding for babies. Previously, it was recommended that children be breastfed for a period of 1 year to ensure receipt of maximum health and wellness benefits (Meek & Noble, 2022); the new recommendation calls for a period of 2 years of breastfeeding alongside the supplementation of complementary foods gradually after the first 6 months.…”
mentioning
confidence: 99%
“…The recommended change to the current breastfeeding protocol was meant to ensure maximal wellness for both the breastfeeding parent and the infant. The recommendation is based on the finding that after a year of breastfeeding, the human milk retains the same amount of nutrients (e.g., protein, lysozyme, and lactoferrin) overall, and, in some cases, the supply is increased (Grote et al, 2016; Meek & Noble, 2022). The WHO (2022) has suggested that breastfeeding is directly linked to children’s survival rates and overall well-being.…”
mentioning
confidence: 99%
See 1 more Smart Citation